(untitled) ("Temas Sociais" Journal, 2024)
With the ageing population, the increase in chronic illnesses, and the consequent growth in dependency situations, it has become imperative to review existing paradigms to address the associated problems effectively. Until 2006, various attempts were made to implement policies to respond to the increased medical and social care demand. In this context, the National Network for Integrated Continuing Care (RNCCI) was created in 2006 and has been subject to significant changes ever since. The RNCCI is currently organised into four types: Convalescence, Medium Duration and Rehabilitation, Long Duration and Maintenance, and Integrated Continued Care Teams. This study focuses on Convalescence Units, analysing the adequacy of hospitalisation times. A quantitative methodology was used, with a questionnaire addressed to Convalescence Units in mainland Portugal and a documentary analysis of RNCCI monitoring reports. The results show that delayed discharges are a significant problem due to clinical and socio-family factors. They constrain the units and unnecessarily prolong patients’ stays in acute hospitals.